Prevalence and Intensity of Non-Specific, Mechanical Low Back Pain in Security Guards and Traffic Wardens of Lahore - Iram Saddique, Tooba Mazhar, Ayesha Arif, Madiha Asghar, Saba Riaz, Aasia Aziz, Iqra Sajjad (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To find out the prevalence and intensity of non-specific, mechanical low back pain (LBP) among traffic wardens and security guards. Study design: A Cross sectional study was designed and data collection was done by convenient sampling. Place and duration: The sample was collected from the traffic wardens and security guards from Cantt area and Johar Town, Lahore from 15th September 2021 to 10th December 2021. Methodology: After approval of from ethical committee the data collection was started. Informed consent was taken. A sample of 200 participants including security guards (SCG) and traffic wardens (TW) meeting the inclusion and exclusion criteria after consent filled a questionnaire about the prevalence of low back pain (LBP). Visual analogue scale and MC Gill pain questionnaire were used. SPSS version 21 was used for data analysis. Data was analyzed in form of frequencies, means, standard deviation and bar charts. Results: The mean age of participants was 32±5.64. Males were 160(80%) in number and 40(20%) were females. The prevalence of LBP was 81.5%. Majority of participants had mild to moderate levels of pain severity (49.8%). Independent sample T test showed significant difference in pain severity between both SCG and TW. (p=0.01; p<0.05). Conclusion: There was high prevalence of Low back pain in security guards and traffic wardens. Mild to moderate intensity of pain was reported in majority of participants. There was significant difference in pain intensities in both populations. Keywords: Low back pain, non-specific backache, musculoskeletal disorders, security guards